If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(2p + 3) = 81 Reorder the terms: 9(3 + 2p) = 81 (3 * 9 + 2p * 9) = 81 (27 + 18p) = 81 Solving 27 + 18p = 81 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + 18p = 81 + -27 Combine like terms: 27 + -27 = 0 0 + 18p = 81 + -27 18p = 81 + -27 Combine like terms: 81 + -27 = 54 18p = 54 Divide each side by '18'. p = 3 Simplifying p = 3
| 37=5m-63 | | 10c^2-33ct+20t^21= | | -7b-12=-4 | | 116=5v+16 | | (4x+5y)+(2x-11y)= | | 6a^2-15a-1=0 | | (5x-3)(x-2)(x+1)X=0 | | 6x+32=122 | | -11(26x-52)=44(-9x+3) | | 6p*3= | | 48/3=x/4 | | 5+3(-2)=-1 | | 30+0.35c=72 | | 3s=3 | | 2.5z=-75 | | 5(2)+3(0)=-1 | | -10t=-8t+10 | | 2.8=2n-5 | | W+3.34=5.64 | | 3x+(k+2)x=1-k | | -9+4d=9+2d | | 16-6(n)=2+n | | 4.8-1.8=0.4y | | -5*-25=25-10*-25 | | 4n^2-35=-4n | | y=43+-10x | | Y-6.8=7.4 | | -4b+4=2 | | y=-10x+43 | | 2x-11=7x+44 | | 83+(-9)=92 | | 10r=5+9r |